2019
DOI: 10.3390/molecules24234208
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Urokinase Plasminogen Activator May Impair β Cells Regeneration and Insulin Secretion in Type 2 Diabetes Mellitus

Abstract: Background: The relationship between urokinase-type plasminogen activator (uPA) and the development of type 2 diabetes mellitus (T2DM) was investigated in the study by using mice and cell models, as well as patients with T2DM. Methods: In mice models, wild-type and uPA knockout (uPA-/-) BALB/c mice were used for induction of T2DM. In cell models, insulin secretion rate and β cell proliferation were assessed in normal and high glucose after treating uPA siRNA, uPA, or anti-uPA antibody. In our clinical study, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…It is assumed that it might be due to the stimulation of beta cell to secrete insulin or it may also be possible due to the regeneration of beta cells of pancreas. Our results corroborate the previously reported research studies of similar kind [30][31][32].…”
Section: Discussionsupporting
confidence: 93%
“…It is assumed that it might be due to the stimulation of beta cell to secrete insulin or it may also be possible due to the regeneration of beta cells of pancreas. Our results corroborate the previously reported research studies of similar kind [30][31][32].…”
Section: Discussionsupporting
confidence: 93%
“…Because reduced insulin release has been reported to be the main symptom during the pathogenesis of T2D [ 21 ], we assessed the effects of ICA on levels of insulin in glucose-treated Min6 cells. We found that ICA significantly and dose-dependently increased high glucose-induced insulin secretion when compared with cells treated with UA alone.…”
Section: Discussionmentioning
confidence: 99%